A Study of the Lipidomic Profiles of the CAL-27 and HOK Cell Lines Using EMS Spectra - Wang, Xue-ying; Zhang, Ting; Guan, Wei-qun; Li, Hua-zhu; Lin, Ling (Frontiers in Oncology, 2021)
Objective We aimed to explore the lipidomic profile of the CAL-27 AND HOK cell lines. Methods In this study, we explored the lipidomic difference between CAL-27 human tongue cancer cell lines and human oral keratinocytes cell lines (HOKs) by nontargeted HPLC-MS lipidomic analysis. Then, we further mined the data through bio-information analysis technology and conducted metabolic pathway analysis to map the most affected metabolites and pathway in the two cell lines. Results: A total of 711 lipids were identified, including 403 glycerophospholipids (GP),147 glycerolipids (GL), and 161 sphingolipids (SP). Comparing the EMS spectrum of the two cell lines in positive/negative ionization modes, the lipid compositions of HOK and CAL27 were similar. The expression of most glycerophospholipid (GP) species in CAL-27 cells had an increasing trend compared with HOK, whereas significantly increased PC were observed (P < 0.05). Significant differences between CAL 27 and HOK cells were shown as a heatmap. Through PCA analysis, we could find noticeably clear separation trends between groups of HOK and CAL-27. Satisfactory clustering trends among HOK and CAL-27 are observed in the scores plot. Conclusion Our study demonstrated the possibilities of describing the lipid profile of HOK cells and CAL-27 cells by untargeted mass spectrum and bio-information analysis.